Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`         1.IF Pth term of an A.P is q and qth tem of an AP is p then prove that (p+q) term is 0`
7 years ago

510 Points
```										let a & d are the first term & common differnece respectively then
pth term = a+(p-1)d = q                       ...............1
qth term = a+(q-1)d = p                     ...............2
1-2
q-p = (p-q)d
d=-1
now
(p+q)th term = a + (p+q-1)d
putting value of a from eq 1
(p+q)th term = q - (p-1)d + (p+q-1)d                  (d =-1)
=0
```
7 years ago
Fawz Naim
37 Points
```										The pth term of an AP is = a+(p-1)d
where a is the first term of the AP and  d is the common difference
as pth term is equal to q therefore q=a+(p-1)d .....1
similarly qth term is equal to p
p=a+(q-1)d .......2
solve the two equations to get the value of a and d. It will come
a=p+q-1
d=-1
now (p+q)th term is =a+(p+q-1)d
put the values of a and d
=(p+q-1)+(p+q-1)(-1)
=(p+q-1)-(p+q-1)
=0

```
7 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details
Get extra Rs. 3,180 off
USE CODE: CHEM20
Get extra Rs. 466 off
USE CODE: CHEM20